ANALISIS PENGALAMAN GURU MATEMATIKA DALAM MEMANFAATKAN ARTIFICIAL INTELLIGENCE SEBAGAI MEDIA PEMBELAJARAN - Marliah; Ayu Nofrida; Ririn Ardiyanti; Qona Asidakiah; Sonya Ayuningsih; Amanda Putri Qolbi; Anisa Sabila Fatihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Artificial Intelligence's (AI) rapid developmenthas drastically changed how education is conducted, especially in the teaching of maths. Teachers no longer use AI merely as an information source but increasingly employ it to design instructional materials, develop assessment tasks, create learning media, and support instructional reflection. This study aims to explore mathematics teachers' experiences in utilizing AI as a learning support tool and to identify its perceived benefits, challenges, and future prospects in educational settings. This study used a phenomenological technique in a qualitative manner. Participants consisted of mathematics teachers from junior high schools, Islamic junior high schools, and vocational high schools who had experience using AI in teaching. Data were collected through an open-ended questionnaire distributed via Google Forms and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that AI is primarily utilized to develop instructional materials, generate assessment questions, design presentation media, and access learning resources more efficiently. Teachers reported improved work efficiency and enhanced creativity in designing mathematics instruction. Nevertheless, challenges remain regarding information accuracy, prompt engineering skills, digital literacy, and the necessity of validating AI-generated outputs. The study concludes that AI has considerable potential to become a professional partner for mathematics teachers, provided that it is implemented critically, ethically, and responsibly.